Participação da via do óxido nítrico e do cálcio no vasorrelaxamento induzido pelo flavonoide 5,7,4 trimetoxiflavona (TMF) em artéria mesentérica superior de rato. - Oliveira Filho, Abrahão Alves de (2012)
The pharmacological effects of ethanol extract (EPC), chloroform phase (FPC) and 5,7,4'-trimethoxyflavone (TMF) from Praxelis clematidea on superior mesenteric artery rings of rats, were studied. Isometric tension experiments revealed that EPC and FPC (0.001 to 1000 μg/mL) promoted concentration-dependent relaxation in mesenteric rings with functional endothelium (EC50 = 27.2 ± 6.4 μg/mL, 41.9 ± 11.8 μg/mL, respectively, n = 7), and these effects were attenuated after removal of the vascular endothelium (EC50 = 141.9 ± 19.4 μg/mL,167.0 ± 30.6 μg/mL, respectively, n = 7), suggesting that both are vasorelaxants secondary metabolites. The TMF (10-12 to 10-3 M), composed mostly isolated FPC, promoted a relaxation in rings with intact endothelium (pD2 = 5.44 ± 0.12, n = 6), concentration dependent manner, with power similar to the effect of quercetin, a flavonoid abundant in the plant kingdom (pD2 = 5.71 ± 0.16, n = 6). After removal of functional endothelium the concentration-response curve for the TMF was shifted to the right, with a decrease in potency, but no change in maximal effect (pD2 = 4.50 ± 0.10, n = 6). The relaxation of the flavonoid was not modified by pre-incubation of indomethacin (10 μM). However, it was attenuated after pre-incubation of L-NAME (100 μM, pD2 = 4.52 ± 0.08, n = 5), PTIO (300 μM, pD2 = 4.62 ± 0.09, n = 5 ) and ODQ (10 μM, pD2 = 4.36 ± 0.11, n = 5) and was reversed in preparations with functional endothelium pre-incubated with L-arginine (1 mM) plus L-NAME (100 μM) (pD2 = 5.85 ± 0.14, n = 5). Demonstrating the non-involvement of COX metabolites and participation of the NOS/NO/CGs pathway in the relaxation produced by TMF. The presence of 20 mM KCl (pD2 = 4.62 ± 0.08, n = 5) and TEA (3 mM; pD2 = 4.28 ± 0.10, n = 5) attenuated the response produced by TMF only in rings with endothelium, demonstrating that this compound produces relaxation through activation of K+ channels to endothelium-dependent. In addition, the use of glibenclamide (10 μM) did not modify the effect of TMF on rings with functional endothelium, but the pre-incubation of 4-aminopyridine (1 mM; pD2 = 4.7 ± 0.08, n = 5) and TEA (1 mM; pD2 = 4.48 ± 0.04, n = 5) attenuated the potency of the flavonoid vasorrelaxant response, suggesting the involvement of the K+ channels to Kv and BKCa type. TMF relaxations in mesenteric rings pre-contracted with 60 mM KCl and inhibited the vasoconstriction induced by CaCl2 concentration dependent manner. The maximum effect of TMF was mitigated by pre-incubation of nifedipine (1 μM, Emáx = 56.0 ± 7.9%, n = 5), indicating that the flavonoid-induced vasodilation is related to the inhibition of the influx of Ca2+ via L-type Cav. In conclusion, these results suggest that the EPC, the FPC and TMF inducing effect vasorrelaxante in mesenteric rings, and that the response produced by the flavonoid involves NOS/NO/CGs pathway, with consequent activation of channels for K+, and inhibition of the influx Ca2+ channels via L-type Cav.